Terrai A Road Damage Reporting Application Based on GIS, Gamification, and Artificial Intelligence - Yuliana Cantikasari; Erni Widarti (Telkom University, 2026)
Slow response to road infrastructure damage is often caused by inefficient conventional reporting systems and a lack of public participation. This research aims to develop Terrai, an innovative road damage reporting system application in Sukoharjo Regency that integrates Geographic Information Systems (GIS), artificial intelligence, and gamification elements. The use of GIS allows for precise mapping of damage locations on digital maps, while Geospatial Artificial Intelligence (GeoAI) technology is implemented to automate the classification of road damage photos into five severity categories through digital image processing. To maintain ongoing public participation, a gamification concept is implemented through points, badges, and a leaderboard. The system development method included field observations, a literature review, prototype design, and interface quality testing. Evaluation was conducted using the System Usability Scale (SUS) method with 30 selected respondents. The test results showed an average score of 87.83, categorizing the application as very good, or very easy to use. Overall, the integration of these three key technologies in Terrai has proven effective in accelerating data verification by relevant authorities, improving reporting accuracy, and providing a robust database for local governments to proactively make road maintenance decisions. The implementation of this system is expected to become a supporting pillar for the realization of smart city governance in Sukoharjo Regency.